MEMBUKA PELUANG BISNIS OLAHRAGA KEBUGARAN (FITNESS DAN SENAM) DALAM MENGEMBANGKAN PROGRAM INDUSTRI OLAHRAGA MELALUI PROGRAM KULIAH KEWIRAUSAHAAN - Wahyunaiti, CH Fajar; Sukamti, Endang Rini; Nugroho, Agung; Kurniawan, Faidillah (Universitas Negeri Yogyakarta, 2010)
The amount of potential perpetrators of sports and various sports- dimensional spheres such as education sport, sports recreation and sports achievement growth opportunities of a sports field of industrial commodities in public life. Looking at the economic reality, one would determine the type of any business will find many obstacles, because the merchandise changes often irrational prices. With the availability of fitness and exercise laboratories that complete the tool can be used for college students and training for the general public. Availability of lecturers teaching 5 courses in physical condition, 9 lecturers as a gymnastics instructor and as a physical trainer consultant in various clubs in Yogyakarta. Encourage the creation of services through the gymnastics and fitness instructor is hope and good opportunities as an alternative to the creation of new jobs for college graduates, which will reduce unemployment. Mentoring activities both in class and in the field carried out as many as 14 x meetings / face to face in accordance with predetermined schedule. Activities, dated Wednesday July 29, 2009 was held Mid Semester as one means of evaluation of activities, dated August 19, 2009 implementation of activities to the field observations of the participants by placing the participants at the appointed place. On the day on Monday and Wednesday 24, August 26 execution of apprenticeship in the field practice schedule has been determined. Evaluations of this program are the participants are required to formulate proposals with business formation assistance from some experts. At the end of final exams conducted activities for the participants to know the final outcome of this entrepreneurship course. From the results of the implementation of field activities and the many benefits, it is deemed there is need for follow-up of this activity either similar or perhaps on the level of activity that much better again